Corruption at the local level in Brazil: decentralization as a pitfall? - Melo Aranha, Ana Luiza (2015)
Recently, Brazil has undergone decentralization processes that could have strengthened the local level in democratic terms. Notwithstanding, the results of these processes were not con-sensual, and corruption persisted as a feature of the Brazilian local level.This paper focuses on the corrupt conduct of municipal public officials who deal with fe- deral funds transferred by the central government. The information collected is part of a profile of corruption in the cities monitored by the federal Executive, revealing both how this phenomenon is distributed in terms of areas and which possible factors can explain the occurrence of corrup- tion in the Brazilian local governments. This paper deals with corruption in the municipalities of Minas Gerais - one of the 26 Brazilian states - from a conception of corruption as the misuse offunds by the political system.The argument focuses on the conduct of municipal public officials who deal with federalfunds transferred to Minas Gerais´ municipalities. In order to conduct this study, we used the reports from the Program of Inspections from Public Lotteries produced by the Office of the Comp- troller General (CGU). First, we built a general profile of the situation in those cities surveyed by the CGU regarding the incidence of irregularities. By doing so, we highlighted which gover- nmental areas would be in a more critical situation. These irregularities, in turn, were taken as proxies for the occurrence of corruption in two different ways. In the first place, according to the amount of irregularities found – which included all kind of irregularities, from formal mistakes to overbilling –, statistical tests were performed in order to establish which factors could be taken as constraints of corruption at the local level. We identified political, social, economic and demo- graphic characteristics that were associated with corruption, in its petty form. On the other hand, we also categorized corruption in a more strict way, considering only the cases in which larger amounts of resources were involved and leaving out the formal irregularities.We demonstrated that not all factors related with corruption in its broader sense (population size, the characteristic of the transfers, municipal characteristics related to income, education and control) kept significantly associated with the incidence of more severe irregularities. We seek to contribute to the debate about whether or not the local level is more susceptible to corruption, which means discussing if decentralization can be understood as a pitfall.